EVALUATION OF THE THERAPEUTIC EFFICACY OF HIGH-INTENSITY PULSED-PERIODIC LASER RADIATION (CLINICAL AND EXPERIMENTAL OBSERVATIONS) - V. V. Sokolov; A. D. Kaprin; A. A. Pankratov; N. M. Lepekhin; Yu. S. Priseko; V. G. Filippov; M. V. Galyetov; A. V. Khrapov (Исследования и практика в медицине, 2016)
From the experience of clinical observations, we have shown a high therapeutic effectiveness of the medical laser KULON-MED in: cosmetics, non-cancer inflammatory diseases of the gastrointestinal tract and cancer (cancer of the stomach and colon) as at different wavelengths, and with different types of photosensitizers. In the area of anti-tumor photodynamic therapy (PDT), based on experimental studies, we have showed the high antitumor (sarcoma S‑37) effectiveness of the laser (with the inhibition of tumor growth of up to 100%) for repetitively pulsed irradiation mode, and for mode fractionation doses laser radiation. In addition, significant differences are shown in the effectiveness of anticancer PDT methods in the application of high-intensity lasers, continuous and pulsed caused fundamental properties of laser radiation characteristics – time structure of the radiation pulses. Thus, for the first time we have shown that the time of high-intensity laser pulses structure significantly affects therapeutic efficacy laser system, and hence on the mechanisms of interaction of laser radiation with biological tissue.